Optimizing the Preparation of Work Plans Using Linear Regression - Astrika, Rahayu; Pardede, Akim Manaor Hara; Sihombing, Anton (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Preparing effective and efficient work plans to achieve regional government strategic goals is often faced with budget management challenges, especially in the face of increasing indicative ceilings. This research optimizes this process at the Langkat Regency Regional Secretariat using the linear regression method. This method evaluates previous work plans and adapts them to regional financial capabilities for more efficient budget use. The research results show that linear regression provides accurate predictions of budget needs, with an error rate (MAPE) of 0.08% and an accuracy rate of 99.92%. It is hoped that this optimization can support regional development goals in a structured and measurable manner.